2016
DOI: 10.1016/j.jri.2015.09.073
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of virus-specific CD8 + memory T cells in decidual tissue

Abstract: The most abundant lymphocyte present in decidual tissue is the CD8(+) T cell. It has been shown that most decidual CD8(+) T cells have an effector-memory phenotype, but expressed reduced levels of perforin and granzyme B compared with the peripheral CD8(+) effector-memory T cells. The specificity of these CD8(+) memory T cells has yet to be determined. One hypothesis is that the decidual memory T cells are virus-specific T cells that should protect the fetus against incoming pathogens. As virus-specific CD8(+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 46 publications
1
45
1
1
Order By: Relevance
“…Seropositive women during late pregnancy demonstrated an accumulation of highly differentiated HCMV-specific T-cells (139). Moreover, increased percentages of HCMV and EBV-specific CD8 + T cells were also found in decidual tissue compared with peripheral blood after uncomplicated pregnancy (142). These decidual virus-specific CD8 + memory T cells were able to produce IFNγ and were restricted to recognize viral peptides presented by HLA-A or HLA-B molecules.…”
Section: Hla-c-restricted Pathogen-specific Cd8 + T Cell Responsesmentioning
confidence: 99%
“…Seropositive women during late pregnancy demonstrated an accumulation of highly differentiated HCMV-specific T-cells (139). Moreover, increased percentages of HCMV and EBV-specific CD8 + T cells were also found in decidual tissue compared with peripheral blood after uncomplicated pregnancy (142). These decidual virus-specific CD8 + memory T cells were able to produce IFNγ and were restricted to recognize viral peptides presented by HLA-A or HLA-B molecules.…”
Section: Hla-c-restricted Pathogen-specific Cd8 + T Cell Responsesmentioning
confidence: 99%
“…Besides the studies of virus-specific CD8+ T cells in maternal blood, a recent study demonstrated increased percentages of HCMV and Epstein Bar virus (EBV)-specific CD8+ T cells in decidual tissue compared with peripheral blood after uncomplicated pregnancy. These virus-specific CD8+ memory T cells were able to produce IFNγ and were restricted to recognize viral peptides in HLA-A or HLA-B molecules (van Egmond et al, 2016). Thus, these CD8+ dT may provide cellular immunity for infected maternal cells that express HLA-A and HLA-B.…”
Section: Anti-viral and Bacterial Immunity By Cd8 T Cells In Pregnancymentioning
confidence: 99%
“…In vitro studies have shown that trophoblasts produce a wide variety of anti-microbial substances 5, 10 and decidual NK cells are able to control cytomegalovirus (CMV) infections 11 . It has also been shown that memory CD8 + T cells specific for CMV and Epstein-Barr virus accumulate in decidual tissues 12 .…”
Section: Introductionmentioning
confidence: 99%